A case of multiple myeloma with navicular bone involvement. Issue 4 (November 2017) - Yildizhan, Esra; Kaynar, Leylagul; Tiren, Nicolette; canoz, Ozlem; Eser, Bulent
Multiple myeloma is a haematological disease caused by proliferation of malignant plasma cells in bone marrow. It frequently has lytic bone lesions. However, involvement of the small bones of the hands and feet is extremely rare. We report a unique multiple myeloma patient with first recurrence in navicular bone after allogenic stem cell transplantation.